AFTA and its implication to the export demand of Indonesian palm oil - Ernawati,; Mohamed Arshad, Fatimah; Shamsudin, Mad Nasir; Mohamed, Zainal Abidin (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2006)
This paper examines the impacts of trade liberalization policy changes (reduction in export duty and import tariff) on the export demand of the Indonesian palm oil. The study utilised an error correction model. The model is simulated by decreasing the export duty and import tariff individually by 10, 30, 50 and 100 percent. To see the combine effect both in export duty and import tariff were simultaneously reduced by 10, 30, 50, and 100 percent. The findings indicate that trade liberalization due to increase domestic price and reduce in world price. Due to the reduction in export duty, the quantity exported to India, China, Europe, and ROW increased by 0.38, 3.77, 0.67 and 4.63 percent respectively. Reduction on import tariff on the exported-quantity to India, China, Europe, and rest of the world increased by 0.25, 2.67, 0.49, and 2.96 percent respectively. And export duty and import tariff reduction by 10 percent increased export to India, China, Europe, and ROW by 0.64,6.23, 1.12, and 7.35 percent, respectively.